The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1021/jp973034a
|View full text |Cite
|
Sign up to set email alerts
|

The 248-nm Excimer-Laser-Ablation Mechanism of Liquid Benzene Derivatives:  Photochemical Formation of Benzyl Radical Leads to Ablation

Abstract: The mechanism underlying 248-nm laser ablation of liquid benzene derivatives (alkyl benzenes, benzyl chloride, benzyl alcohol) was revealed by means of transient absorption spectroscopy. One characteristic in the present liquid system is that the ablation threshold can be correlated not to the boiling point at all but to the photochemical reactivity of β-bond cleavage. In the spectroscopic measurement, the benzyl-radical formation was confirmed upon ablation, and its concentration was quantitatively evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
10
40
0
Order By: Relevance
“…The reactions also affect the ablation threshold value that is lower in the system with photochemistry as compared to the system with vibrational relaxation only. Indeed, it was discussed by Tsuboi et al [1,2] that, in the ablation of the liquid chlorobenzene sample the estimated temperature at the ablation threshold (97 • C) is below the boiling point (132 • C) signifying the contribution of photochemical fragmentation processes. Conversely, for benzene in which only vibrational relaxation of the molecules occurs, the estimated temperature is higher than the boiling point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactions also affect the ablation threshold value that is lower in the system with photochemistry as compared to the system with vibrational relaxation only. Indeed, it was discussed by Tsuboi et al [1,2] that, in the ablation of the liquid chlorobenzene sample the estimated temperature at the ablation threshold (97 • C) is below the boiling point (132 • C) signifying the contribution of photochemical fragmentation processes. Conversely, for benzene in which only vibrational relaxation of the molecules occurs, the estimated temperature is higher than the boiling point.…”
Section: Resultsmentioning
confidence: 99%
“…Tsuboi et al [1,2] have reported on 248 nm laser ablation of liquid benzene and benzene derivatives such as toluene, benzyl chloride, chlorobenzene and benzyl alcohol. Based on the values of temperature estimated for the threshold fluence, they concluded that the ablation of benzene is induced by explosive boiling of the overheated liquid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific percentage has been observed experimentally for 248-nm irradiation of a molecular beam of chlorobenzene. 112 The dependence of the amount of material removed per laser pulse versus fluence for these two systems is shown in Figure 14. Regardless of the presence of photochemistry, both systems exhibit two distinct mechanisms of ejection, desorption, and ablation, separated by the ablation threshold.…”
Section: Photochemical Effectsmentioning
confidence: 99%
“…Though the threshold depends on the liquid absorption, there is no linear correlation as the pyrene doping causes a sevenfold increase of the absorption but the threshold is reduced only little. The laser-induced decomposition of halogenated hydrocarbons, however, can result in halogen radicals [57,58,60,61] and can, therefore, contribute to the etching [58,62]. However, this does not explain the lower etch rate if at halogenated organics the same processes occur.…”
Section: Etch Characteristics For Different Materials and Absorbing Lmentioning
confidence: 99%